RESILIENCE AND SELF-CONCEPT IN NEW STUDENTS OF THE GUIDANCE AND COUNSELING STUDY PROGRAM - Eka Aryani (Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: This study aims to determine the relationship between resilience and self-concept in new students of the Guidance and Counseling Study Program, Mercu Buana University, Yogyakarta. New students have their own challenges in life. When individuals enter college, individuals experience various changes in social relationships, and financial problems. The hypothesis in this study is that there is a positive relationship between resilience and self-concept in new students. The subjects in this study were new students of the guidance and counseling study program, 33 students. The measuring instrument used in this research is the Self-Concept Scale and the Resilience Scale. The results of the study were analyzed using the product moment correlation technique. The results of the correlation coefficient (rxy) = 0.613 with p = 0.000 (p < 0.05). This shows that there is a significant positive relationship between self-concept and resilience in new students of the guidance and counseling study program. From the results of this study, it can be concluded that self-concept has a positive contribution to resilience so that the higher the self-concept, the higher the resilience of students. Individuals who have a high self-concept will be more confident, have an optimistic attitude, and always have a positive attitude towards everything. Individuals are also able to appreciate themselves and see positive things that can be done for success in the future.